2023
DOI: 10.3389/fgene.2022.981471
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 inhibits spermatogenesis in the testes by inducing cellular senescence

Abstract: Introduction: COVID-19 (SARS-CoV-2) has been linked to organ damage in humans since its worldwide outbreak. It can also induce severe sperm damage, according to research conducted at numerous clinical institutions. However, the exact mechanism of damage is still unknown.Methods: In this study, testicular bulk-RNA-seq Data were downloaded from three COVID-19 patients and three uninfected controls from GEO to evaluate the effect of COVID-19 infection on spermatogenesis. Relative expression of each pathway and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Oxidative stress and inflammatory cytokines, particularly TNF and IL1β, are known to be detrimental to spermatogonial stem cells and spermatozoa by triggering dysregulated sperm ROS production and inducing apoptosis ( Motrich et al, 2006 ; Guazzone et al, 2009 ; Paira et al, 2022 ). In addition, reported data indicate that SARS-CoV-2 infection would inhibit spermatogenesis by inducing testicular cell senescence through MAPK signaling pathway, which is mainly triggered by stress responses like inflammation and oxidative stress ( Wang et al, 2022 ). Moreover, recently reported data show that death of undifferentiated spermatogonia is caused by inflammatory mediators released during the infection rather than by the infection itself ( Giannakopoulos et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammatory cytokines, particularly TNF and IL1β, are known to be detrimental to spermatogonial stem cells and spermatozoa by triggering dysregulated sperm ROS production and inducing apoptosis ( Motrich et al, 2006 ; Guazzone et al, 2009 ; Paira et al, 2022 ). In addition, reported data indicate that SARS-CoV-2 infection would inhibit spermatogenesis by inducing testicular cell senescence through MAPK signaling pathway, which is mainly triggered by stress responses like inflammation and oxidative stress ( Wang et al, 2022 ). Moreover, recently reported data show that death of undifferentiated spermatogonia is caused by inflammatory mediators released during the infection rather than by the infection itself ( Giannakopoulos et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the omics studies on SARS-CoV-2 infection and its consequence on testis focused on understanding the expression pattern of ACE2 in various types of cells. Transcriptomic analysis revealed the negative impact of COVID-19 on spermatogenesis and the dysregulation of molecular pathways linked to the immune response, which in turn may alter spermatogenesis by inducing testicular cell senescence through the MAPK signaling pathway [73]. Further, impaired spermatogenesis was supported by histopathological changes such as the presence of degenerated germ cells (GCs) in the lumen of seminiferous tubules that indicated negative a impact of SARS-CoV-2 infection on GC development [74].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a negative correlation has been demonstrated between seminal IL-1β and TNF concentrations and sperm concentration and total sperm count in SARS-CoV-2 infected patients, with the highest IL-1β levels detected in the group of patients with crypto-azoospermia [ 37 ]. Furthermore, recently reported evidence has revealed that the infection with SARS-CoV-2 would be able to suppress spermatogenesis by inducing senescence in testicular cells through the MAPK pathway, which is mainly elicited by stress responses such as inflammation and oxidative stress [ 38 ]. Noteworthy, the production of exaggerated levels of cytokines and chemokines could also trigger an autoimmune reaction with pathological consequences in the testis like inflammation-induced inhibition of spermatogenesis [ 31 ],[ 59 ].…”
Section: Discussionmentioning
confidence: 99%